The Crisis of Imprisonment: Protest, Politics, and the Making of the American Penal State, 1776-1941 - Lichtenstein, Alex (Labour / Le Travail, 2009)
The article reviews the book, "The Crisis of Imprisonment: Protest, Politics, and the Making of the American Penal State, 1776-1941," by Rebecca M. McLennan.
Keywords: BOOKS – Reviews; CONVICT labor; CRISIS of Imprisonment: Protest; Politics & the Making of the American Penal State 1776-1941; The (Book); History; MCLENNAN; Rebecca M.; Nonfiction